2020
DOI: 10.1109/access.2020.2966590
|View full text |Cite
|
Sign up to set email alerts
|

Maize Carotenoid Gene Locus Mining Based on Conditional Gaussian Bayesian Network

Abstract: How to mine the gene locus for maize carotenoid components is an important research problem in biology study. Along with the rapid development of high-throughput biotechnologies, we have produced a large number of maize multi-omics data, including genome, transcriptome, metabolome, phenotype, etc. How to conjointly analyze these continuous and discrete data, and thus to mine the genetic loci that control the maize carotenoid components have a very important biological significance. In this work, we use the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…For instance, Zhao et al (2020) [ 135 ] chose the most optimal hyperparameters and kernel function for the SVM model to explore the genomic-based prediction performance in pigs and maize. To gain the possible significant loci, Liu et al (2020) constructed the maize gene, SNP locus, and carotenoid components network using the conditional Gaussian Bayesian network learning method [ 120 ]. Lv et al (2022) proposed minmax concave penalty (MCP) regularization for sparse deep neural networks (DNN-MCP), which can provide the optimal sparse structure for DNN and then greatly improve their ability to predict genomes, especially for the genomes of three quantitative traits [ 187 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhao et al (2020) [ 135 ] chose the most optimal hyperparameters and kernel function for the SVM model to explore the genomic-based prediction performance in pigs and maize. To gain the possible significant loci, Liu et al (2020) constructed the maize gene, SNP locus, and carotenoid components network using the conditional Gaussian Bayesian network learning method [ 120 ]. Lv et al (2022) proposed minmax concave penalty (MCP) regularization for sparse deep neural networks (DNN-MCP), which can provide the optimal sparse structure for DNN and then greatly improve their ability to predict genomes, especially for the genomes of three quantitative traits [ 187 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers have used CGBN in other fields of research; for example, Hu [20] used CGBN to process seismic data with a mixture of discrete and continuous variables, then applied CGBN to the prediction of earthquakes in Canterbury from 2010 to 2011; the experimental results showed that the prediction performance of CGBN was better than that of algorithms such as neural networks and support vector machine. Liu in [21] used CGBN to mine gene loci for carotenoid components of maize, finding that CGBN exhibited better performance than other algorithms in the experiment. In this paper, CGBN is used to learn isolated feature variables (variables that do not affect the target variable) from healthcare expenditure data, then regression algorithms are used to learn the data with the isolated variables removed.…”
Section: Related Workmentioning
confidence: 99%